An Experimental Study on Quality Maintenance in Purchasing - Hernando Budiman (Soegijapranata Catholic University, 2022)
Quality in purchasing process is important for sustainability of the producer-consumer relationship. Purchasing department in a company should not only buy materials, but also should consider consistency of quality of the materials purchased and maintain good relationship with the suppliers in relation with production problems. The main task of a purchasing department is to buy materials in the right quantity, quality, time, and price as well as to deal with services provided by the suppliers. Quality of purchased materials can be evaluated based on the materials received from the suppliers. Quality is considerably better if the acceptance rate of the purchased materials is higher. The rate depends on comparison of the total materials sent by the supplier to those that are accepted by the receiving department. This study evaluates work process in the purchasing department of a cigarete company regarding to the quality of materials provided by the suppliers and proposes development actions based on SMART analysis. The resulted development was then implemented in the department for three semesters to know whether the development really bring the benefits in purchasing process in the company. The result indicates that that suggested actions were able to improve the quality performance.